Helping Skills: The Empirical Foundation. 2001
DOI: 10.1037/10412-006
|View full text |Cite
|
Sign up to set email alerts
|

Methodological examination of videotape-assisted reviews in brief therapy: Helpfulness ratings, therapists intentions, client reactions, mood, and session evaluation.

Abstract: One of the continuing issues in process research has concerned the impact that the methods and measures used have on the data collected and the conclusions drawn (see Hill, 1991, andLambert & Hill, 1994, for reviews). For example, an ongoing concern has been that data collection may be unduly intrusive and may alter the quality or nature of the therapeutic interaction. Other concerns have been expressed about the reliability and validity of process measures and the effects of situational variables on data. Bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Using a singleitem measure is a common practice to investigate client perceptions of therapy (e.g., Fridman, 2010;Fuller & Hill, 1985;Horvath, Marx, & Kamann, 1990), with face-valid items typically yielding high levels of predictive validity (Hoyt, 2002). Single-item measures of helpfulness are also known to be stable over time, consistent between clients and therapists, and predictive of session outcome measures (Hill et al, 1994). They are also commonly used as a treatment outcome (e.g., Hill, et al, 1994;Elliott, 1985;Liddle, 1996) and have been found to hold concurrent validity with clients' overall satisfaction with their therapist (Conte, Buckley, Picard, & Karasu's, 1994).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a singleitem measure is a common practice to investigate client perceptions of therapy (e.g., Fridman, 2010;Fuller & Hill, 1985;Horvath, Marx, & Kamann, 1990), with face-valid items typically yielding high levels of predictive validity (Hoyt, 2002). Single-item measures of helpfulness are also known to be stable over time, consistent between clients and therapists, and predictive of session outcome measures (Hill et al, 1994). They are also commonly used as a treatment outcome (e.g., Hill, et al, 1994;Elliott, 1985;Liddle, 1996) and have been found to hold concurrent validity with clients' overall satisfaction with their therapist (Conte, Buckley, Picard, & Karasu's, 1994).…”
Section: Methodsmentioning
confidence: 99%
“…Single-item measures of helpfulness are also known to be stable over time, consistent between clients and therapists, and predictive of session outcome measures (Hill et al, 1994). They are also commonly used as a treatment outcome (e.g., Hill, et al, 1994;Elliott, 1985;Liddle, 1996) and have been found to hold concurrent validity with clients' overall satisfaction with their therapist (Conte, Buckley, Picard, & Karasu's, 1994).…”
Section: Methodsmentioning
confidence: 99%